Training to improve the "Big Three" - Crowther, G. (2001)
Article deals with the three main performance components for endurance sports: maximal oxygen consumption (VO2max), lactate threshold, and running economy, their importance and the training for their development. Summary: Interval workouts at vVO2max and tempo runs at the lactate threshold are both key ingredients in the training programs of competitive distance runners. In designing a training schedule for a particular individual or team, however, the specificity-of-training principle must again be considered. In short, one's key workouts should be tailored somewhat to the pace, distance, and terrain of the race one is training for. For example, workouts at race pace are almost always a good idea regardless of what that pace happens to be, and long runs may be much more important for marathoners than for 5K specialists. Nevertheless, when pondering these important issues, we should not forget what the data tell us: "long" intervals and tempo runs are probably our best training tools for maximizing VO2max, lactate threshold, running economy, and overall fitness. (This article originally appeared in the March 2001 issue of Northwest Runnermagazine.)